Rancang Bangun Sistem Informasi Desa Berbasis Website Menggunakan Metode Scrum (Studi Kasus: Desa Penusupan, Kabupaten Tegal) - Akhdan Syarif Hidayatullah, Dias; Agung Prabowo , Dedy; Euclides Wahyu Nugroho , Nicolaus (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Penusupan Village is located in Pangkah District, Tegal Regency. The limited use and implementation of information system technology in local governance have resulted in the village not yet having an optimal information system service for its residents. For example, population data management is still unclear—there are instances where names of deceased individuals remain listed as eligible voters, which should have already been addressed by the village's administrative services. This issue became the basis for designing an information system for Penusupan Village. An information system is a set of components that processes, stores, analyzes, and distributes information, consisting of people, technology, and work procedures to achieve specific goals. The proposed information system for Penusupan Village is developed in the form of a website, aimed at supporting data management and providing accessible information services for the community. The system design is carried out using the Scrum methodology as the research approach. Scrum is a process framework used to manage complex product development. The Penusupan Village information system website utilizes the Laravel framework for the back-end and Bootstrap for the front-end, supported by the PHP programming language. The use of PHP is intended to ensure the website functions dynamically while enabling faster, more secure, and more efficient development.